Compartmentalization of the Yeast Meiotic Nucleus Revealed by Analysis of Ectopic Recombination - Schlecht, Hélène B. (Genetics Society of America, 2004)
As yeast cells enter meiosis, chromosomes move from a centromere-clustered (Rabl) to a telomere-clustered (bouquet) configuration and then to states of progressive homolog pairing where telomeres are more dispersed. It is uncertain at which stage of this process sequences commit to recombine with each other. Previous analyses using recombination between dispersed homologous sequences (ectopic recombination) support the view that, on average, homologs are aligned end to end by the time of commitment to recombination. We have undertaken further analyses incorporating new inserts, chromosome rearrangements, an alternate mode of recombination initiation, and mutants that disrupt nuclear structure or telomere metabolism. Our findings support previous conclusions and reveal that distance from the nearest telomere is an important parameter influencing recombination between dispersed sequences. In general, the farther dispersed sequences are from their nearest telomere, the less likely they are to engage in ectopic recombination. Neither the mode of initiating recombination nor the formation of the bouquet appears to affect this relationship. We suggest that aspects of telomere localization and behavior influence the organization and mobility of chromosomes along their entire length, during a critical period of meiosis I prophase that encompasses the homology search.